SEJARAH BERDIRINYA PT. LPPPI DAN PENGARUHNYA TERHADAP PERKEMBANGAN SOSIAL-EKONOMI MASYARAKAT KELURAHAN TEBINGTINGGI KECAMATAN TEBINGTINGGI KABUPATEN TANJUNG JABUNG BARAT PROVINSI JAMBI TAHUN (1994-2015) - Mestika Sari; Kamarruddin Oemar; Bunari ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The purpose of this research is (1) to know the history stand up PT. LPPPI at tebingtinggi of subdistrict tebingtinggi of regency tanjung jabung barat jambi province in the year 1994-2015 (2) to know the influence PT. LPPPI in the field of social-economic of society village at tebingtinggi of subdistrict tebingtinggi of regency tanjung jabung barat jambi province in the year 1994-2015 (3) to know the negative influence stand up PT. LPPPI at tebingtingi of subdistrict tebingtinggi of regency tanjung jabung barat jambi province in the year 1994-2015 (4) to know the program of corporate social responsibility (CSR) in village tebingtinggi of subdistrict tebingtinggi of regency tanjung jabung barat jambi province in the year 1994-2015. In this research method qualitative where this matter will give the complete information so that be of benefit to science. Result from this research is village at tebingtinggi of subdistrict tebingtinggi regency jabung barat jambi province in the year 1994-2015 experience of a growth in the field of social-economic influence by standing PT. LPPPI with the existence a caring program to society where that company stand up with the program the corporate social responsibility (CSR)Key Words: PT. LPPPI Tebingtinggi Village, Socio-Economic